Development of Learning Web to Improve Junior High School Students' Scientific Literacy - Robi Mulya Gunawan; Bibin Rubini; Irvan Permana (Universitas Pakuan, 2022)
This study aims to produce a learning web that can improve the scientific literacy of junior high school students. This study used the Research and Development method with a 4D design modified into 3D: the definition stage, the design stage, and the development stage. The research subjects were 35 eighth-grade students in junior high school. The instruments used in this study consisted of a multiple-choice test to capture the achievement of the content, students' science competence and knowledge, an attitude scale to capture students' scientific attitudes, and student response questionnaires to the learning web. The results showed that learning science using the learning web could improve scientific literacy skills in the medium category. Based on the results and data analysis, the increase in learning outcomes calculated using the N-Gain Test with an average gain of 55.89% is in the medium criteria, indicating a positive difference between learning outcomes before and after learning activities. The responses from students and teachers to the learning web are generally positive and supportive of its development and use.